Cerium oxide nanoparticles protect against chondrocytes and cartilage explants from oxidative stress via Nrf2/HO-1 pathway in temporomandibular joint osteoarthritis - Xiong, Liping; Bao, Han; Li, Size; Gu, Deao; Li, Yuyang; Yin, Qianwen; Li, Wen; Miao, Leiying; Liu, Chao (Frontiers in Bioengineering and Biotechnology, 2023)
Oxidative stress is closely linked to the etiology of temporomandibular joint osteoarthrosis ((TMJ-OA) and is an important therapeutic target. Cerium oxide nanoparticles (CNPs) have been broadly studied owing to their powerful antioxidant properties and potential preventive and therapeutic effects against chronic diseases. The current study was designed to explore the protective effects of CNPs on the progression of TMJ-OA and their potential mechanisms. We detected the ability of CNPs to eliminate reactive oxygen species (ROS) in chondrocytes. Moreover, their protective effects on chondrocytes were detected in the level of gene and protein. Furthermore, TUNEL assay, histology and safranin O-fast green staining were used to detect the beneficial effects of CNPs on cartilage explants. The mechanism of CNPs, protecting condylar cartilage by reducing inflammation, was further explored by knocking down the Nuclear factor-erythroid 2-related factor (Nrf2) gene. CNPs could reduce the ROS levels in chondrocytes and cartilage explants and reverse the IL-1β-induced imbalance of cartilage matrix metabolism and apoptosis. The protective effects of CNPs on cartilage were lost after key antioxidant factors including Nrf2 and heme-oxygenase 1(HO-1) were significantly reduced. In conclusion, this study demonstrated for the first time that activating the Nrf2/HO-1 signaling pathway by CNPs might have therapeutic potential for TMJ-OA.